2019
DOI: 10.2196/14886
|View full text |Cite
|
Sign up to set email alerts
|

Social Media Recruitment of Marginalized, Hard-to-Reach Populations: Development of Recruitment and Monitoring Guidelines

Abstract: BackgroundSocial media can be a useful strategy for recruiting hard-to-reach, stigmatized populations into research studies; however, it may also introduce risks for participant and research team exposure to negative comments. Currently, there is no published formal social media recruitment and monitoring guidelines that specifically address harm reduction for social media recruitment of marginalized populations.ObjectiveThe purpose of this research study was to investigate the utility, successes, challenges, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 43 publications
(53 reference statements)
1
48
0
Order By: Relevance
“…A number of homophobic comments were posted which may have discouraged potential participants from engaging with the advertisements. While we did moderate these comments in order to remove discriminatory or bullying content (36), it is difficult to do this in real-time and the comments may have been seen regardless. Third, collecting contact information from someone who screened eligible does not guarantee that that individual will enroll as an RCT participant.…”
Section: Discussionmentioning
confidence: 99%
“…A number of homophobic comments were posted which may have discouraged potential participants from engaging with the advertisements. While we did moderate these comments in order to remove discriminatory or bullying content (36), it is difficult to do this in real-time and the comments may have been seen regardless. Third, collecting contact information from someone who screened eligible does not guarantee that that individual will enroll as an RCT participant.…”
Section: Discussionmentioning
confidence: 99%
“…From January to February 2019, TGNC people living in the Southeast U.S. were recruited online via targeted Facebook advertisements to complete an online survey. This recruitment approach is an evidence-based method documented to successfully recruit stigmatized groups into research projects [18][19][20][21].…”
Section: Recruitmentmentioning
confidence: 99%
“…Given the increased popularity of online media and information platforms, many researchers are using web-based tools to recruit participants for medical, psychological, and sociological research studies (especially for stigmatized and hard-to-reach groups). Previous studies have shown that online methods can successfully recruit and manage people who are humiliated or discriminated against because of race, sexual orientation, or mental health status [ 17 , 18 ]. Our results confirmed recent literature regarding online recruitment of hard-to-reach people and expanded the scope of recruitment and management to the study population of sexual dysfunction and gut microbe research .…”
Section: Discussionmentioning
confidence: 99%